Knowledge on pain management and associated factors on it among the nurses working in Teaching Hospital, Jaffna - Thirothay, A.; Varnan, S.; Jegapragash, V.; Yaanuthy, T. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: Pain management is a key component of patient satisfaction and wellbeing in acute care settings. Nurses spend more time with patients than any other members of the health care team and have an important role in pain assessment and management. Inadequate knowledge is a significant clinical problem leading to inappropriate and inadequate pain management practices. Objective: To assess the knowledge and associated factors on pain management among the nursing officers working in Teaching Hospital, Jaffna. Methodology: A descriptive, cross-sectional study was conducted among 346 nursing officers working in Teaching Hospital Jaffna by using a pre-designed and validated self-administered questionnaire. Systematic random sampling method was used to identify the participants. Data were analysed with SPSS 25 and descriptive statistics were used to describe the variables and chi squared test was performed to identify the associated factors. The ethical clearance was obtained from Ethics Review Committee of Faculty of Medicine. Results: Mean age of the study participants was 31.55(±8.236). Half of them (50.9%) had less than three years’ experience as a nurse. Among the participants only 14.2% of the nurses had good knowledge, 39.0% of the nurses had moderate knowledge and 46.8% of the nurses had poor knowledge. Most participants were knowledgeable on pain is one of the vital signs (92.2%) and use non pharmacological techniques along with pain medication (84.7%). Knowledge on pain management had significant association with learned the theory from nursing educational program (P=0.017). Conclusion: Nearly half of the participants had poor knowledge on pain management. It is recommended to have regular training sessions to update their knowledge on pain management.
Keywords: Pain management; Nurses; Knowledge; Teaching hospital jaffna